The Purpose of the First World War War Aims and Military Strategies - Afflerbach, Holger (De Gruyter Oldenbourg, 2015)
Ten million soldiers died during the First World War. But why, and for what reason? The Great War is widely seen as a "pointless carnage" (Pope Benedict XV). Was there a point, at least in the eyes of the political and military decision makers? International specialists analyse the hopes and expectations of the political and military leaders and try to explain why the contemporaries thought that they had to fight the Great War.